Changes in daily nursing needs and self‐care capability of people with diabetes after in‐hospital treatment for foot complications: A descriptive study - Magdalena Annersten Gershater; Slobodan Zdravkovic; Targ Elgzyri (Wiley, 2024)
Abstract Aim A limited number of studies discuss the changes in patients' self‐care skills and needs for assisted self‐care after discharge from in‐patient treatment due to diabetes foot ulcer‐related complications. The aim of this study was to examine the ability to perform self‐care and needs for assisted nursing interventions at hospital discharge, compared to pre‐admission, for people with diabetes admitted and treated for foot ulcer‐related complications. Design Retrospective patient record study. Methods A retrospective assessment was done on the medical records of a total of 134 patients with diabetes consecutively admitted to a specialist in‐patient unit due to foot ulcer complications, between 1 November 2017 and 30 August 2018. Data on daily self‐care needs and home situations at admission and discharge were recorded. Results The median age was 72 years (38-94), 103 (76.9%) were men and 101 (73.7%) had diabetes type 2. The median length of admission was 10 days (2-39). Infection was the most common cause of admission (51%), with severe ischaemia in 6%, and a combination of both in 20% of patients. Surgical treatment was performed in 22% and vascular intervention in 19% of patients. The percentage of patients discharged to their home without assistance was 48.1% compared to 57.5% before admission, discharge to home with assistance was 27.4% versus 22.4% before admission and 9.2% were discharged to short‐term nursing accommodation versus 6% before admission. Three patients died during their stay in hospital. The need for help with medications increased from 14.9% of patients at admission to 26.7% at discharge and for mobility assistance from 23.1% to 35.9%. Social services at home were increased in 21.4% of patients at discharge.